Improved Stability and Exciton Diffusion of Self‐Assembled 2D Lattices of Inorganic Perovskite Nanocrystals by Atomic Layer Deposition. Issue 20 (30th July 2020) - Lorenzon, Monica; Jurow, Matthew; Hong, Min Ji; Lu, Yi‐Hsien; Barnard, Edward S.; Salmeron, Miquel; Liu, Yi; Penzo, Erika; Schwartzberg, Adam M.; Weber‐Bargioni, Alexander
Abstract: Colloidal inorganic perovskite nanocrystals (PNCs) are solution‐processable optoelectronic materials whose emission can be easily tuned via both size and composition while maintaining high photoluminescence quantum yield. Despite their relative defect tolerance, they suffer from photoinduced damage and degradation under ambient conditions. The lack of long‐term stability is addressed by investigating how a ≈3 nm transparent ceramic coating applied onto a thin layer of close‐packed PNCs via atomic layer deposition (ALD) affects the exciton mobility across the PNCs. Samples coated via both thermal and plasma ALD are compared, as well as an uncoated one. Exciton diffusion measurements yield a record value for all samples, up to λD = 480 ± 24 nm, one order of magnitude larger than the previously reported values for chalcogenide quantum dots and more than two times larger than what was previously found for the PNCs. Moreover, the ALD‐coated samples show stable photoluminescence intensity and energy over 1 year time span. The measurement approach allows for discerning minimal variations in the local luminescence and qualitatively correlating them to the samples' morphology. Hence, it is shown that PNCs coated with an ultrathin ALD film become a very versatile optoelectronic material that can be employed in devices beyond proof of principle. Abstract : The exciton diffusion across a self‐assembled, close‐packed monolayer of cesium lead bromide perovskite nanocrystals coated with an ultra‐thin layer of aluminum oxide is investigated. A Förster resonance energy transfer‐enabled diffusion length of up to 480 nm is found, and spatially and spectrally resolved measurements of the diffusion profile are provided.